Analysis of the Juridical Review Regarding the Action of Checking Mobile Phones by Police Officers During Patrols - Muda, Mahmud; W. Badu, Lisnawaty; Y. Mantali, Avelia Rahmah (Universitas Negeri Gorontalo, 2024)
The purpose of this study is to find out the provisions governing the inspection of cellphones by police officers during patrols. The research method used is a normative research method using a literature study approach. The results of this study are about the Raimas Backbone Team who violated the law against Article 1 number 18 of Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP) concerning Body Search is an investigator's action to conduct an examination of the suspect's body and or clothes to search for objects that are strongly suspected of being on his body or carrying with him, to be confiscated. In this case it is clear that the actions of the Raimas Backbone Team who carried out the search were beyond the authority given to them, because basically in the Criminal Procedure Code Number 8 of 1981 Article 6 paragraph 1. Investigators are: (a) ). State police officials of the Republic of Indonesia, (b). Certain civil servant officials who are given special authority by law.